PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNINGN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI RUPA DI SMA NEGERI 1 KOTO XI TARUSAN - RESTI RAHMA YUNI, Drs. Jamilus, M.Pd., Ph.D., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2016)
The following research is purposed to described the influence of of Discovery Learning model towards learning’s result of students in the subjects of Art in SMA Negeri 1 Koto XI Tarusan. Thisresearch is using quantitative method with an quasi-experimental model. the instrument is using learning’s result test in the form of learning outcomes. Afterwards, the data is processed by using SPSS program version 16.00. Based on hypothesis testing by using SPSS program version 16.00, obtained that t (count) is 4,195 and t (table) is 1,699 with significance of (α = 0,05). It shows that there is significance difference between two classes. Therefore, it is concluded that applying discovery learning model has a positive influence toward learning’s result of students in the subjects of Art in SMA Negeri 1 Koto XI Tarusan. Kata Kunci: Model pembelajaran discovery learningdan hasil belajar